Making employment rights effective: issues of enforcement and compliance (Oxford, 2012)
"There has been an enormous expansion of individual employment rights in Britain but their practical impact in terms of delivering fairer workplaces can be questioned. Taking as its starting point the widespread acknowledgement of problems with the major enforcement mechanism, the Employment Tribunals, this collection brings together experts from law, sociology and employment relations to explore a range of alternative regulatory and non-regulatory approaches to enforcement and to securing compliance and to consider factors affecting variation in the extent to which legal rights have meaning and impact at the workplace. Thus this book addresses issues key to contemporary policy and academic debate."